PERANCANGAN SISTEM INFORMASI RETENSI REKAM MEDIS PASIEN RAWAT INAP DI RUMAH SAKIT BHAYANGKARA KOTA BENGKULU - Maharani; Wikey Yulanda (Jurnal Infokes, 2021)
This study aims to find out the design of the medical record retention information system of inpatients at Rumah Sakit Bhayangkara Kota Bengkulu. Data collection techniques are done by means of observation and interview, while the method of software development using is the waterfall model method. The design of a medical record retention information system refers to the processing of data retention until the creation of a report. System design methods use Flowmap, DFD (Data Flow Diagram) and ERD (Entity Relation Diagram) and are implemented with microsoft visual programming language Basic.Net using Visual Studio 2010 software and Microsoft Access as DBMS (Database Management System). Based on the results of the analysis that has been done on the medical record retention system implemented at Kebonjati Hospital can be concluded as follows: (1) The medical record retention system that runs today still uses a manual system so that the implementation of retention is less effective and efficient. (2) Not optimal medical record retention information system because in the selection of inactivated files, officers must see one by one the last date of treatment on the active medical record rack, then if the patient file is categorized as inactive, then the file is separated, inputted and stored in an inactivated room. Keywords : Information Systems, Retention, Visual Basic.Net, Hospitalization, Visual Studio 2010